The Social And Psychological Effects On Palestinian Women Under Repeated Israeli Incursions In Tubas Governorate (Journal of the College of Basic Education, 2026)
This study aimed to identify the social and psychological effects experienced by Palestinian women in light of the repeated Israeli incursions in Tubas Governorate. The study population consisted of all women in Tubas Governorate, and the study sample comprised 60 women. They were selected randomly to include the study variables. The researcher used the descriptive-analytical method, as the descriptive method suits the nature of the study problem and its objectives. The study results showed that Palestinian women in Tubas Governorate suffer significant psychological and social effects resulting from the repeated Israeli incursions. Concerning psychological effects, it was found that Palestinian women feel unsafe, sorrowful, and distressed about what happens, and pessimistic about the future. Regarding social effects, it was found that Palestinian women increasingly neglect their social relationships both at work and outside due to the incursions. Also, it was found that the children's needs are numerous and cannot be met under these circumstances, and managing household affairs has become difficult due to poor economic conditions. In light of the results yielded by the study, the researcher suggests providing group and individual psychological support services for women who feel insecure and fearful, and launching programs aimed at addressing chronic grief and pessimism about the future among affected women.